A Study Of Employees' Commitment In Customer Network Operation Division In Telekom Malaysia - Hussin, Abd Razak (2000)
This study sought to understand employees' commitment in Customer Network Operation Division in Telekom Malaysia and also factors that affect their commitment so that it can be useful inputs to the organisation in developing strategies on how to continual